UNDERSTANDING SELF-CONCEPT ABOUT SEXUAL HARASSMENT IN CLASS VII STUDENTS OF SMPN 1 SEMPU - Shofiyah Rizqi Lafensa; Heriberthus Wicaksono; Harwanti Noviandari (International Jurnal of Education Schoolars, 2022)
This study aims to determine the relationship between self-concept and sexual harassment in grade VII students at SMPN 1 Sempu. This research uses a quantitative approach with descriptive research methods. The subjects in this study were 60 students selected by random sampling technique. The results of this study showed a significant relationship between self-concept and sexual harassment. This can be seen from the results of the F test carried out, the F test results show that the significant value obtained is smaller than 0.05, (<0.01 < 0.05).